Bottom-contact fisheries disturbance and signs of recovery of precious corals in the Northwestern Hawaiian Islands and Emperor Seamount Chain. (April 2023) - Baco, Amy R.; Morgan, Nicole B.; Brendan Roark, E.; Biede, Virginia
Highlights: Coralliid octocorals were used as indicator species to assess seamount recovery state. Both species had reduced abundance and smaller colony size in disturbed areas. Some recovery was observed but was uneven among sites and species. Recovery, where observed, supports return to the original state. Two Still Trawled seamounts are not able to recover under current levels of fishing. Abstract: Deep-sea precious corals in the octocoral family Coralliidae are among the dominant benthic megafauna at depths of 300–600 m on seamounts of the Northwestern Hawaiian Islands and lower Emperor Seamount Chain. Pleurocorallium secundum and Hemicorallium laauense were once abundant enough on these seamounts to support a targeted coral fishery in the 1960s and 1970s. Significant trawl finfish fisheries were also occurring in the same time frame on the same seamounts. Because they had high enough abundance to support a targeted fishery for two decades, these two coralliid species must have been a key component of the baseline community on these seamounts. Therefore, they provide an ideal indicator species for testing effects of large-scale disturbance and potential for recovery in deep-sea coral and seamount communities. Using AUVs and submersibles, we explored seamounts outside the US EEZ that are still actively fished by trawl, seamounts within the US EEZ that were historically trawled but have been protected since the establishment of the EEZ, and seamounts that have never been trawled, to determine population distributions and colony sizes for the targeted coral species. P. secundum had only one individual on actively trawled seamounts and occurred in low abundance on most Recovering seamounts. H. laauense was present in a few areas in Recovering and Still Trawled seamounts. Colony size distributions for H. laauense showed a smaller median size on Recovering and Still Trawled seamounts compared to the Never Trawled sites. P. secundum had a slightly smaller median colony size on the Recovering Seamounts than on the Never Trawled seamounts. These results indicate a reduction in abundance for both species in disturbed areas with some unexpected potential for recovery on protected seamounts. Recovery was uneven among sites and species with SE Hancock and Koko showing the largest populations of H. laauense among the Recovering and Still Trawled seamounts, respectively. P. secundum showed much less recovery, with its largest population on Bank 11 in the Recovering seamounts. Kammu, one of the primary seamounts of the coral fishery, had only a single coralliid observed. The other primary target, Yuryaku, had a small number of coralliids in a steeply sloped area. These two Still Trawled seamounts do not appear to be able to recover under the current levels of fishing pressure.